Physicochemical Characteristics and Microbiological Quality of the Topside and Longissimus Dorsi of Indonesian Local Buffalo Meat - Noraimah Binti Sulaiman; Cece Sumantri; Irma Isnafia Arief; Cahyo Budiman (Faculty of Animal Science, Universitas Gadjah Mada, 2020)
The physicochemical characteristics and microbiological quality of buffalo meat are influenced by differences in muscle type. This study aimed to evaluate the physiochemical characteristic and microbiological quality of the topside (active muscle) and longissimus dorsi (passive muscle) of Indonesian local buffalo meat. Samples used in this study were buffalo meat from local swamp buffalo, aged more than four years old on the topside and longissimus dorsi. This study used a completely randomized design, with three repetitions in each treatment. All data were analyzed using analysis of variance (ANOVA). The result of the study on the topside and longissimus dorsi area showed a significant difference in the pH and cholesterol levels of the buffalo meat. The longissimus dorsi area had a lower level of pH and cholesterol compared to the topside area. Furthermore, this longissimus dorsi meat has a higher color, protein, ash, fat, essential amino acid, and lactic acid bacterial (BAL) content than the topside meat. However, the topside meat had higher carbohydrate, essential fatty acid, Escherichia coli (E. coli) and Staphylococcus aureus (S. aureus) content compared to the longissimus dorsi meat. Longissimus dorsi meat had better physicochemical characteristics and microbiological quality than the topside meat